2013
DOI: 10.4137/jcd.s11034
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between Apoptosis and Autophagy: Molecular Mechanisms and Therapeutic Strategies in Cancer

Abstract: Both apoptosis and autophagy are highly conserved processes that besides their role in the maintenance of the organismal and cellular homeostasis serve as a main target of tumor therapeutics. Although their important roles in the modulation of tumor therapeutic strategies have been widely reported, the molecular actions of both apoptosis and autophagy are counteracted by cancer protective mechanisms. While apoptosis is a tightly regulated process that is implicated in the removal of damaged or unwanted cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
77
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(84 citation statements)
references
References 239 publications
(408 reference statements)
6
77
0
1
Order By: Relevance
“…Numerous studies showed that apoptosis or a reciprocal action between apoptosis and autophagy is the major process to control cell fates [8,9,12,24,25]. Interestingly, the findings of this study showed that bufadienolides KB, KA, and BC do not induce cellular apoptosis but only induced cell autophagy.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Numerous studies showed that apoptosis or a reciprocal action between apoptosis and autophagy is the major process to control cell fates [8,9,12,24,25]. Interestingly, the findings of this study showed that bufadienolides KB, KA, and BC do not induce cellular apoptosis but only induced cell autophagy.…”
Section: Discussionsupporting
confidence: 54%
“…In some cases, autophagy and apoptosis modulate each other to control cell fates [24,25,29]. It has also been known that autophagy acts as a pro-death pathway and is called autophagic cell death which is different from apoptotic cell death [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from their physiological role in the maintenance of cellular homeostasis, apoptosis and autophagy serve as important targets of tumor therapeutics. [23][24][25][26][27][28][29] Whereas apoptosis is implicated in the removal of damaged or unwanted cells, autophagy is a cellular catabolic pathway that is involved in lysosomal degradation and recycling of proteins and organelles, and is therefore considered as an important survival mechanism for both normal cells and cancer cells in response to metabolic stress or chemotherapy. In hematologic malignancies, autophagy can either act as a chemoresistance ©2015 Ferrata Storti Foundation.…”
Section: Introductionmentioning
confidence: 99%
“…Basal levels of autophagy are required for cellular homeostasis. Autophagy is upregulated under various cellular stresses, such as infection, starvation, organelle damage, and protein aggregation [13, 14]. Autophagy has complicated functions in different stages of cancer [15].…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is a catabolic process by which cytoplasmic components, such as damaged organelles, aged proteins, and damaged proteins, are sequestered by a double-membrane autophagosome, and delivered to the lysosome for degradation [13]. Basal levels of autophagy are required for cellular homeostasis.…”
Section: Introductionmentioning
confidence: 99%